PEDAGOGICAL-PSYCHOLOGICAL FEATURES OF DEVELOPMENT OF GENERAL CULTURAL COMPETENCE OF EDUCATORS OF PRESCHOOL EDUCATIONAL ORGANIZATIONS (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This article talks about the pedagogical and psychological features of the development of universal competences of educators of preschool educational organizations. The concepts of "competence", "competence", "professional competence" are defined.